Quaternary interglacial sediments as possible natural sources of arsenic and molybdenum anomalies In stream sediments In Lithuania - Zinkutė, Rimantė; Baltrūnas, Valentinas; Taraškevičius, Ričardas; Karmaza, Bronislavas; Stakėnienė, Rimutė; Šeirienė, Vaida; Kisielienė, Dalia (Journal of Environmental Engineering and Landscape Management, 2015)
Geochemical investigations were conducted on Quaternary interglacial sediments in order to reveal if they can be a natural source of 10 potentially harmful chemical elements: As, Ba, Cr, Cu, Mn, Mo, Ni, Pb, V and Zn. Determination of the total contents of elements in 680 samples was performed by EDXRF analysis. The content of Ni, Cu, Pb, Ba in all analyzed samples was lower than maximum permissible concentrations (MPC) for soil, the content of Zn, V, Cr, Mn exceeded MPC values only in several samples (≤4%). The highest percentage of anomalous samples where MPC was exceeded was characteristic of Mo (21%) and As (12.6%). Therefore, interglacial sediments, especially enriched in organic matter and other sorbents, comprise one of the possible natural sources of Mo and As. It is probable that they contribute to As and Mo anomalies in stream sediments in Lithuania.First published online: 22 Dec 2014